A circularly polarized metantenna for 5G and RF energy harvesting applications - Bikash Ranjan Behera; Harikrishna Paik; Mohammed H. Alsharif; Peerapong Uthansakul; Monthippa Uthansakul (Engineering Science and Technology, an International Journal)
We present a broadened, circularly polarized, high-gain surrogate model-assisted differential evolution for antenna synthesis (SADEA)-driven metantenna to fulfill the necessity of 5G communication applications at a sub-6 GHz. Initially, we consider a linearly polarized (LP) printed monopole antenna at Stage 1. To attain circular polarization (CP), a metallic strip is utilized as the dynamic switching mechanism to connect one of the parasitic conducting strips to a partial ground plane and short it out. So, this particular geometry expands upon Stages 2 and 3, proposing a straightforward mechanism to transition from LP to CP. In Stage 4, the objective is to make it a suitable candidate for RF energy harvesting, which is a bigger part of the 5G communication applications. Hence, from the application perspective, we achieve the performance trade-offs by increasing the CP gain, impedance (10-dB BW), and axial bandwidth (3-dB BW). This is achieved by placing the SADEA-tuned metasurface layer at a height of 0.33λ ∘, is directly beneath the CP monopole radiator. Stage 4 is fabricated on an FR-4 substrate and offers a measured 46.41% 10-dB BW, 18.42% 3-dB BW, a peak CP antenna gain of > 8.35 dBic, and an antenna efficiency of > 75% in the desired operating band. These outcomes are beneficial for technical applications in wireless technology, ensuring the stability of RF networks through the incorporation of smart metasurfaces. Their usage provides individualized, efficient, and typical management of EM waves in accordance with the ambient RF conditions of the desired bands, bringing about an exemplary shift in a wireless communication environment in response to ever-increasing requirements.